Intelligent Management on the Home Consumers with Zero Energy Consumption - Kazem Khani; Mohammad Iman Ghiasi (IAES Indonesian Section, 2017)
The energy and environment crisis has forced modern humans to think about new and clean energy sources and in particular, renewable energy sources. With the development of home network, the residents have the opportunity to plan the home electricity usage with the goal of reducing the cost of electricity. In this regard, to improve the energy consumption efficiency in residential buildings, smart buildings with zero energy consumption were considered as a proper option. Zero-energy building is a building that has smart equipment whose integral of generated and consumed power within a year is zero. In this article, smart devices submit their power consumption with regard to the requested activity associated with the user’s time setting for run times and end times of the work to the energy management unit and ultimately the time to start work will be determined. The problem’s target function is reducing the energy cost for the consumer with taking into account the applicable limitations.